In-chamber thermocatalytic tar cracking and syngas reforming using char-supported NiO catalyst in an updraft biomass gasifier - James R, Arthur M.; Yuan, Wenqiao; Boyette, Michael D.; Wang, Donghai; Kumar, Ajay (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: The objective of this study was to evaluate the performance of an in-chamber tar cracking and syngas reforming unit. This unit was composed of a two-stage tubular reactor placed within the combustion zone of an updraft biomass gasifier. Heat generated in the exothermic combustion reactions of biomass gasification drove tar cracking and syngas reforming in the tubes, eliminating the need of external heating. The performance of the unit was evaluated using char-supported NiO catalysts and was found to be very effective in tar removal and syngas composition enhancement. A tar removal rate of 95% was achieved at 0.3 s residence time and 10% nickel loading. This condition also gave syngas high-heating value increment of 36% (to 7.3 MJ/m3). The effect of gas residence time and Ni loading on tar removal and syngas composition of the unit was also studied. Gas residence of 0.2-0.3 s and Ni loading of 5%-10% were found appropriate to produce clean syngas with tar content appropriate for industrial applications (smaller than 0.6 g/m3) in an updraft biomass gasifier without external heating.Keywords: biomass gasification, tar cracking, syngas reforming, nickel catalyst, char catalystDOI: 10.3965/j.ijabe.20140706.011Citation: James A, Yuan W, Boyette M D, Wang D, Kumar A. In-chamber thermocatalytic tar cracking and syngas reforming using char-supported NiO catalyst in an updraft biomass gasifier. Int J Agric & Biol Eng, 2014; 7(6): 91－97.